Perencanaan Strategis Sistem Informasi pada Perusahaan Kosmetik Menggunakan Metode Ward and Peppard (Pusat Riset dan Inovasi Nasional, 2025)
This study explores strategic information system (IS) planning within a local cosmetics company facing the challenges of the digital era and global competition. The primary issues identified include the lack of integrated IT systems, limited digital infrastructure, and difficulty responding to rapid market dynamics. The aim is to develop an IS strategy aligned with the company’s business objectives to enhance operational efficiency and competitiveness. A qualitative case study approach is employed, utilizing the Ward and Peppard methodology to analyze both internal and external business environments. SWOT and Value Chain analyses are applied to identify strengths, weaknesses, opportunities, and threats, while Five Forces and IS/IT environmental analysis support the development of targeted strategies. Key findings highlight significant potential in product innovation and digital marketing, yet stress the need for better-integrated IT systems, particularly in data management and business process efficiency. The final outcome includes recommended development of integrated IS solutions: sales systems, inventory tracking, cashier systems, and payroll applications, all prioritized using the McFarlan Strategic Grid. The study concludes that the Ward and Peppard method is effective in guiding companies to formulate adaptive, measurable, and sustainable IS strategies, equipping them to face future challenges in the cosmetics industry.